1992
DOI: 10.1128/aac.36.12.2741
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of once-daily amikacin in various combinations with cefepime, aztreonam, and ceftazidime against Pseudomonas aeruginosa in an in vitro infection model

Abstract: The pharmacodynamics of once-daily amikacin administered as monotherapy and in combination with aztreonam, ceftazidime, and cefepime against Pseudomonas aeruginosa ATCC 27853 and clinical isolate 16690 (moderately susceptible to ceftazidime) were investigated with an in vitro model of infection over a 24-h period. Monotherapy with aztreonam, ceftazidime, and cefepime and combinations of aztreonam with cefepime or ceftazidime were also studied. MICs and MBCs were determined for viable organisms at 24 h to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Consistent with in vitro synergy studies, aztreonam was found to enhance the activity of other beta-lactams (Lister et al, 1998;McGrath et al, 1992;Van Laethem et al, 1984). In a P. aeruginosa in vitro PD model, aztreonam combined with ceftazidime or cefepime led to a shorter time required to achieve 99.9% reduction in log 10 CFU/mL than monotherapy (McGrath et al, 1992).…”
Section: In Vitro Pharmacodynamic (Pd) and In Vivo Efficacy Data On Dmentioning
confidence: 51%
See 4 more Smart Citations
“…Consistent with in vitro synergy studies, aztreonam was found to enhance the activity of other beta-lactams (Lister et al, 1998;McGrath et al, 1992;Van Laethem et al, 1984). In a P. aeruginosa in vitro PD model, aztreonam combined with ceftazidime or cefepime led to a shorter time required to achieve 99.9% reduction in log 10 CFU/mL than monotherapy (McGrath et al, 1992).…”
Section: In Vitro Pharmacodynamic (Pd) and In Vivo Efficacy Data On Dmentioning
confidence: 51%
“…Particularly impressive results were found in 2 separate E. coli rabbit meningitis models, where mecillinam plus ampicillin led to a significant decrease in bacterial titers compared to each agent alone (P b 0.01) (Schaad et al, 1982;Scheld et al, 1979). Third-generation cephalosporins also led to improved activity when used with other beta-lactams Tsuchiya, 1981a, 1981b;Lister et al, 1998;McGrath et al, 1992;Shyu et al, 1987;Zinner et al, 1981). In a P. aeruginosa rat peritonitis model, significantly higher survival rates were seen when ticarcillin was combined with ceftazidime than when each agent was used alone (P b 0.05) (Shyu et al, 1987).…”
Section: In Vitro Pharmacodynamic (Pd) and In Vivo Efficacy Data On Dmentioning
confidence: 86%
See 3 more Smart Citations